2021
DOI: 10.3390/pr9101840
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Characterization and Antioxidant Capacity of Laurus nobilis L. Leaf Extracts Obtained by Green and Conventional Extraction Techniques

Abstract: Laurus nobilis L. is an evergreen Mediterranean shrub whose leaves have been known for various health-promoting effects mainly attributed to polyphenols. Microwave- (MAE) and ultrasound-assisted extraction (UAE) are green extraction techniques that enable effective isolation of polyphenols from plant material. Therefore, the aim of this research was to optimize the extraction conditions of MAE (ethanol percentage, temperature, extraction time, microwave power) and UAE (ethanol percentage, extraction time, ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 84 publications
8
25
0
Order By: Relevance
“…The influence of the irradiation power and temperature must not be excluded, since Rincon et al [ 70 ] performed the extraction at 90 °C and 500 W, which might have caused degradation of thermosensitive phenolic compounds over a prolonged time. In accordance, Dobroslavić et al [ 68 ] reported that the increase of temperature from 40 to 80 °C resulted in higher TPC; however, with an irradiation time prolonged from 10 to 15 min, a stagnation of the TPC was observed, which was brought by the authors into connection with possible thermal degradation. The authors have also observed a decline in the TPC when an irradiation power higher than 400 W was applied.…”
Section: Extraction Of Phenolic Compounds From L Nobilis Leavessupporting
confidence: 65%
See 4 more Smart Citations
“…The influence of the irradiation power and temperature must not be excluded, since Rincon et al [ 70 ] performed the extraction at 90 °C and 500 W, which might have caused degradation of thermosensitive phenolic compounds over a prolonged time. In accordance, Dobroslavić et al [ 68 ] reported that the increase of temperature from 40 to 80 °C resulted in higher TPC; however, with an irradiation time prolonged from 10 to 15 min, a stagnation of the TPC was observed, which was brought by the authors into connection with possible thermal degradation. The authors have also observed a decline in the TPC when an irradiation power higher than 400 W was applied.…”
Section: Extraction Of Phenolic Compounds From L Nobilis Leavessupporting
confidence: 65%
“…However, in their study, the TPC after 15–30 min was lower than the yield that Muniz-Marquez et al [ 44 ] achieved after 6 min with 50% ethanol. This indicates that use of 50% ethanol under MAE conditions of Muniz-Marquez et al [ 44 ] is more time-efficient, which can be substantiated by results recently reported by Dobroslavić et al [ 68 ] where 10 min was optimal during the extraction or L. nobilis leaf polyphenols with 50% ethanol. The presence of water in ethanol increases the dielectric constant of the system, which could result in an increased extraction yield by improving the swelling of the plant material and therefore increasing the surface contact of the matrix and solvent [ 95 , 96 ].…”
Section: Extraction Of Phenolic Compounds From L Nobilis Leavessupporting
confidence: 65%
See 3 more Smart Citations